Comparison of Surgical Time and Clinical Outcomes for Intravenous Regional Anesthesia (IVRA) versus Wide-Awake Local Anesthesia No Tourniquet (WALANT) in Open Carpal Tunnel Release Surgery: A Comparative Study - Guler, Ali; Senol, Yigit Can (Asian Journal of Neurosurgery, 2025)
This study aimed to compare the efficacy and safety of two anesthetic techniques in patients undergoing carpal tunnel release surgery: intravenous regional anesthesia (IVRA) and the wide-awake local anesthesia no tourniquet (WALANT) technique.A retrospective observational dual-center study was conducted, including 102 patients diagnosed with moderate-to-severe carpal tunnel syndrome (CTS) unresponsive to conservative treatment. Outcomes were assessed using the visual analog scale (VAS) for pain and the Duruoz Hand Index (DHI) for hand functionality. Comparisons were made based on age, gender, preoperative VAS scores, incision length, and surgical procedure duration.The outcomes of the WALANT (n = 51) and IVRA (n = 51) techniques in CTS surgery were compared. The IVRA group had a shorter operation time (2.49 ± 0.50 minutes) and faster return to daily activities (10.13 ± 9.50 days) compared with the WALANT group (operation time: 7.27 ± 1.35 minute, return to daily activities: 17.64 ± 2.52 days) (p < 0.05). Additionally, postoperative analgesic requirements were significantly lower in the IVRA group (8/51; 15.6%) than in the WALANT group (37/51; 72.5%) (p < 0.05). Both groups showed significant postoperative improvements in VAS and DHI scores (p < 0.05), with the IVRA group demonstrating a greater improvement in DHI scores (14.76 ± 0.43) compared with the WALANT group (12.76 ± 0.45) (p < 0.05).IVRA with small incisions demonstrated superior outcomes in CTS surgery compared with WALANT, including shorter operation times, faster recovery, and reduced postoperative analgesic requirements. These findings suggest that IVRA may be a more favorable option for both patients and surgeons in carpal tunnel release surgery.
Keywords: carpal tunnel syndrome; IVRA; regional anesthesia; WALANT; wide awake local anesthesia